Exploring reaction to subliminal codes in print advertising - Judeel, Ilse; Mulder, Dalme; Beelders, Tania (Department of Communication Science, University of the Free State, 2010)
Advertising is a huge industry and has a perpetual influence on any economy. Although visual communication lies at the core of advertising effectiveness, the power of visual communication does not nearly receive the attention it deserves. One of the more controversial areas of visual communication in advertising is called subliminal advertising. In subliminal advertising, covert visual messages/images are used to communicate with the audience. This type of communication occurs below the threshold of an individual’s awareness. However, the question whether subliminal signs do communicate or persuade has been debated for several decades. In this study, eyetracking research was combined with qualitative research to determine the reaction of individuals when being exposed to print advertisements containing subliminal embeds. The study did not aim to explain if, how or why this subliminal embeds might work or not; only whether they can be seen. According to the results, subliminal embeds in print advertising can only be seen once pointed out to the respondents. However, a large number of respondents’ eye-gaze were fixed on the subliminal embeds, even though they did not report seeing it.